2017
DOI: 10.1016/bs.pmbts.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases in Normal Pregnancy and Preeclampsia

Abstract: Normal pregnancy is associated with marked hemodynamic and uterine changes that allow adequate uteroplacental blood flow and uterine expansion for the growing fetus. These pregnancy-associated changes involve significant uteroplacental and vascular remodeling. Matrix metalloproteinases (MMPs) are important regulators of vascular and uterine remodeling. Increases in MMP-2 and MMP-9 have been implicated in vasodilation, placentation and uterine expansion during normal pregnancy. The increases in MMPs could be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
177
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(195 citation statements)
references
References 437 publications
(679 reference statements)
9
177
1
8
Order By: Relevance
“…It is widely accepted that the circumferential enlargement, along with axial elongation of the pregnant UA is mediated by substantial changes in several local genes [3]. Studies from our lab and others have shown explicit evidence for vascular specific transcriptional activation of unique genes (e.g., MMPs and TIMPs and estrogen receptor-ESR2) in gestational uterine vascular remodeling [45][46][47][48]. In the current study, the overall global changes in the uterine vasculature transcriptome activate a majority of pathways related to the local and peripheral immune response, which may help to tolerate the semi-allogeneic fetus [49].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is widely accepted that the circumferential enlargement, along with axial elongation of the pregnant UA is mediated by substantial changes in several local genes [3]. Studies from our lab and others have shown explicit evidence for vascular specific transcriptional activation of unique genes (e.g., MMPs and TIMPs and estrogen receptor-ESR2) in gestational uterine vascular remodeling [45][46][47][48]. In the current study, the overall global changes in the uterine vasculature transcriptome activate a majority of pathways related to the local and peripheral immune response, which may help to tolerate the semi-allogeneic fetus [49].…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, chymotrypsin-like serine endopeptidases are major serine proteases in human arteries responsible for angiotensin-converting enzyme (ACE)-independent production of angiotensin II, which play a significant role in vascular remodeling and contraction [62]. MMPs are another group of endopeptidases that degrade various proteins in the extracellular matrix (ECM), including collagen and elastin [45], which determines vascular remodeling, angiogenesis, and the systemic changes in blood pressure in healthy pregnancy [45,63]. On the other hand, the attenuated UA methyltransferase activity, which is involved in DNA/RNA and histone methylation, is shown to contribute to the decrease in the KCNMB1 promoter CpG methylation in pregnant ovine UA [64].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MMP9 has been linked not only to sPTB, but also to PPROM and PE across a number of fetal and maternal tissues and at a variety of time points during pregnancy [63][64][65][66][67].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, plasmin is the activator of multiple functional proteins. For instance, plasmin activates the generation of over 7 matrix metalloproteinases (MMPs) 6 , which directly participate in the processes of tissue remodeling, cancer progression, pregnancy, etc [7][8][9] . Beyond its fibrinolytic property, plasmin also has anti-coagulative effects by degrading factors V and VIII, thus blocking coagulation cascades 10 .…”
Section: The Fibrinolytic Systemmentioning
confidence: 99%